1996
DOI: 10.1007/bf02174028
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the double genome structure of modern sugarcane cultivars (Saccharum spp.) by molecular cytogenetics

Abstract: Cultivated sugarcane clones (Saccharum spp., 2n=100 to 130) are derived from complex interspecific hybridizations between the species S. officinarum and S. spontaneum. Using comparative genomic DNA in situ hybridization, we demonstrated that it is possible to distinguish the chromosomes contributed by these two species in an interspecific F1 hybrid and a cultivated clone, R570. In the interspecific F1 studied, we observed n + n transmission of the parental chromosomes instead of the peculiar 2n + n transmissio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
269
2
8

Year Published

1998
1998
2014
2014

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 320 publications
(287 citation statements)
references
References 30 publications
8
269
2
8
Order By: Relevance
“…As the region where North Indian and Chinese cultivars are encountered is outside the natural distribution range of S. robustum, the scenario of Brandes provides the simplest explanation of the data: Noble cultivars were transported by man to mainland Asia where they hybridized with local S. spontaneum. It is likely that resulting clones are first-generation hybrids because no -or very few-interspecific chromosome exchanges have been detected with GISH, in contrast with modern cultivars (D'Hont et al, 1996). Owing to mitochondrial haplotypes, it is most likely that, in all cases, Noble clones acted as females and S. spontaneum clones acted as males in founding crosses (D'Hont et al, 1993).…”
Section: Origin Of North Indian and Chinese Cultivarsmentioning
confidence: 99%
“…As the region where North Indian and Chinese cultivars are encountered is outside the natural distribution range of S. robustum, the scenario of Brandes provides the simplest explanation of the data: Noble cultivars were transported by man to mainland Asia where they hybridized with local S. spontaneum. It is likely that resulting clones are first-generation hybrids because no -or very few-interspecific chromosome exchanges have been detected with GISH, in contrast with modern cultivars (D'Hont et al, 1996). Owing to mitochondrial haplotypes, it is most likely that, in all cases, Noble clones acted as females and S. spontaneum clones acted as males in founding crosses (D'Hont et al, 1993).…”
Section: Origin Of North Indian and Chinese Cultivarsmentioning
confidence: 99%
“…or S. barberi Jesw (Miller et al, 2005). Sugarcane cultivars have a complex, aneuploid and polyploid genome, which contains 100-120 chromosomes (D'Hont et al, 1996). Due to the complex nature of the genome, molecular analysis of sugarcane is not an easy task; however, different molecular techniques have been employed in sugarcane breeding and trait-related marker studies, including random amplified polymorphic DNA (RAPD) for genetic diversity (Harvey and Botha, 1996;Nair et al, 2002;Pan et al, 2003a), amplified fragment length polymorphism (AFLP) for genome mapping and QTL analysis of yield components (Hoarau et al, 2002;Lima et al, 2002), and restriction fragment length polymorphism (RFLP) in genetic diversity and genome complexity (Lu et al, 1994;Jannoo et al, 1999;Silva and Bressiani, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Modern cultivars generally have between 100 and 130 chromosomes (Grivet and Arruda, 2002). In situ hybridization studies have suggested that modern cultivars inherit approximately 80% of their chromosomes entirely from S. officinarum, approximately 10% entirely from S. spontaneum, and approximately 10% as the result of recombination among the remaining ancestral species (D'Hont et al, 1996).…”
Section: Introductionmentioning
confidence: 99%